Peran Intelijen Keamanan Dalam Pencegahan Dan Penanggulangan Tindak Pidana Terorisme - Suman Sirait; Junaidi Abdillah (Jurnal USM Law Review)
This study aims to analyze the role and strategy of the Security Intelligence Division (Intelkam) of the Bangka Belitung Islands Police in preventing and countering terrorism in an archipelagic region vulnerable to the transit of extremist networks. The research background stems from the high terrorism threat level in Indonesia and the strategic geographic position of Bangka Belitung, which increases the risk of radical infiltration. The urgency lies in the critical need to strengthen the role of regional intelligence as the front line in early detection and counter-radicalization efforts. The research method employs a normative juridical approach, utilizing legal and conceptual frameworks, and is analyzed through a descriptive-qualitative lens. Findings indicate that Intelkam Babel has implemented both preventive and repressive strategies, such as digital surveillance, monitoring of ex-terror convicts, and collaboration with community leaders, although challenges remain regarding human resources, budget constraints, and inter-agency coordination. The novelty of this study lies in its focus on island-based regions and localized approaches to deradicalization strategies. The study concludes that Intelkam's strategies must be enhanced through technological modernization, capacity building, integrated intelligence systems, and expanded locally-rooted deradicalization programs. It is recommended that the implementation be supported by a continuous monitoring and evaluation (M&E) system to ensure sustained and effective terrorism prevention at the regional level.